2015
DOI: 10.1007/s40279-015-0361-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Recreational Soccer Effective for Improving $$ \dot{V}{\text{O}}_{2\;\hbox{max} } $$ V ˙ O 2 max ? A Systematic Review and Meta-Analysis

Abstract: BackgroundSoccer is the most popular sport worldwide, with a long history and currently more than 500 million active participants, of whom 300 million are registered football club members. On the basis of scientific findings showing positive fitness and health effects of recreational soccer, FIFA (Fédération Internationale de Football Association) introduced the slogan “Playing football for 45 min twice a week—best prevention of non-communicable diseases” in 2010.ObjectiveThe objective of this paper was to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
134
5
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(163 citation statements)
references
References 61 publications
21
134
5
3
Order By: Relevance
“…These results parallel those referring to criterion validity in both the untrained and trained status that have shown a moderate association between HR 2min and VO 2max . The recreational football training intervention implemented in this study was successful in producing large improvements in aerobic fitness, in line with previously published studies addressing different populations . Despite the reported large (range 25‐44%) decrease in HR 2min across the field tests, the magnitude of test changes was only small by comparison with VO 2max inter‐individual changes.…”
Section: Perspectivessupporting
confidence: 87%
See 2 more Smart Citations
“…These results parallel those referring to criterion validity in both the untrained and trained status that have shown a moderate association between HR 2min and VO 2max . The recreational football training intervention implemented in this study was successful in producing large improvements in aerobic fitness, in line with previously published studies addressing different populations . Despite the reported large (range 25‐44%) decrease in HR 2min across the field tests, the magnitude of test changes was only small by comparison with VO 2max inter‐individual changes.…”
Section: Perspectivessupporting
confidence: 87%
“…The study was devised with the aim of examining the sustainability of low‐impact test procedures to evaluate the aerobic fitness status of recreational football players during the training process. This with the purpose of implementing, where necessary, training load adjustments to support clinically relevant (3.5 mL·kg −1 ·min −1 ) improvements in VO 2max . The results of this study provided evidence of an association between Yo‐Yo tests’ HR 2min and VO 2max in this population of recreational players, both in the baseline criterion validity (moderate associations) and in its confirmatory evaluation in the post‐intervention retest (small to moderate associations).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In recreational football studies, significant increments in aerobic fitness (VO 2max and intermittent high‐intensity performance) were reported as a training effect of playing small‐sided games at an average intensity of 78%‐85% of HR max [mode 82% HR max ]. It has been suggested that permanence (~20% of total match time) at intensities above 90% of individual HR max during actual match play was probably the cause of the marked improvements observed in aerobic fitness and intermittent high‐intensity performance in recreational football‐based training interventions .…”
Section: Introductionmentioning
confidence: 99%
“…The second type of football (leisure) has also been called recreational, and it is based on small sided games (i.e., 4vs4, 5vs5) played in reduced pitches with different number of players [7]. Different studies have showed that recreational football can produce improvements in VO2 max, body fat, blood pressure, bone health, and cardiac function [9,10,11,12]. There exists another type of football organization that falls between the categories of professional and recreational/leisure football with thousands or even millions of participants worldwide: amateur football.…”
Section: Introductionmentioning
confidence: 99%